Prawa Człowieka . raport, no. 8, 1989 - Komitet Helsiński w Polsce, [EIC Marek A. Nowicki] (Wydawnictwo Społeczne KOS, 1989)
Creation and circulation: From issue no. 9(1 grudnia 1990) published legally